Implementasi Penanaman Pendidikan Agama Islam pada Aspek Al-Qur’an dan Akidah di TPQ Fattuhul Qulub Distrik Doyo Baru - Amin Mustofa; Siti Rokhmah; Asep Rosadi (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
This study aims to describe the implementation of instilling Islamic Religious Education values in the aspects of the Qur’an and Aqidah at TPQ Fattuhul Qulub, Doyo Baru District. The background of this research is based on the importance of Islamic religious education in shaping children’s character and morals from an early age amid the decline in the morality of the younger generation. TPQ, as a non-formal educational institution, has an important role in instilling Islamic values through learning the Qur’an, aqidah, and morals. However, in its implementation, several obstacles are still found, such as the low understanding of students regarding religious values, varying abilities in reading the Qur’an, and the lack of support from family and community environments.This study employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation at TPQ Fattuhul Qulub, Doyo Baru District. The focus of the research includes the planning, implementation, and evaluation processes of instilling Islamic Religious Education values in the aspects of the Qur’an and Aqidah.The results of the study indicate that the instillation of Islamic Religious Education values has been carried out through structured stages of planning, implementation, and evaluation. The learning process was conducted using the methods of Iqra’, tahsin, tahfidz, talaqqi, lectures, role modeling, habituation, and exemplary stories. In the Qur’anic aspect, students were guided to read the Qur’an according to tajwid rules and memorize short surahs, while in the Aqidah aspect, students were taught the pillars of faith, the attributes of Allah and His Messenger, and the formation of Islamic morals. The evaluation results showed improvements in Qur’anic reading skills, memorization, understanding of aqidah, and changes in students’ religious behavior, such as becoming more disciplined, polite, and diligent in worship. This success was supported by the exemplary behavior of the teachers and the involvement of parents in the learning process.